2004
DOI: 10.1002/art.20340
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the synovial inflammatory response through activation of mitogen‐activated protein kinases and nuclear factor κB using ligation of CD40 on CD14+ synovial cells from patients with rheumatoid arthritis

Abstract: Objective. To determine the signal transduction pathways in CD14؉ synovial cells from patients with rheumatoid arthritis (RA) after CD40 ligation, and to examine their role in amplifying synovial inflammation in affected joints.Methods. Expression of messenger RNA was analyzed using quantitative reverse transcriptionpolymerase chain reaction. Cytokines and chemokines were measured using enzyme-linked immunosorbent assay. Activation of kinases was detected using Western blotting. Nuclear translocation of NF-B w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…The reduction in TNF␣ and IL-6 expression is likely to be a direct consequence of CD40 down-regulation. T cells from patients with RA express abundant CD40L (37), and CD40-CD40L interactions have been shown to regulate macrophage activation and production of inflammatory cytokines such as TNF␣ and IL-6 locally in the joints (38)(39)(40). Moreover, Nov038 delivers CD40-ASO to myeloid DCs, major regulators of the immune system processes leading to immunity or tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in TNF␣ and IL-6 expression is likely to be a direct consequence of CD40 down-regulation. T cells from patients with RA express abundant CD40L (37), and CD40-CD40L interactions have been shown to regulate macrophage activation and production of inflammatory cytokines such as TNF␣ and IL-6 locally in the joints (38)(39)(40). Moreover, Nov038 delivers CD40-ASO to myeloid DCs, major regulators of the immune system processes leading to immunity or tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokine/chemokine synthesis and secretion require the activation of MEK/ERK and NF-B pathways. The importance of CD40 signaling through MEK/ERK MAPK family members in inflammatory responses of monocytes and macrophages (28), synovial cells (20), and human proximal tubule cells (21) is well recognized. To study CD40-mediated activation of this pathway in ␤-cells, we began our experiments using NIT-1 cells (29) because these are an acceptable surrogate of primary ␤-cells, given the limited availability and cost of human or NHP islets for research.…”
Section: Diabetes Vol 55 September 2006mentioning
confidence: 99%
“…Previous reports have shown that a significant number of genes are induced by CD40 in nonimmune cells, including genes associated with costimulation signals (42), cytokine secretion (10,20,43), apoptosis induction (44), cell survival (45), and inflammation (46). Earlier studies showed that CD40 signaling results in the activation of the MEK/NF-B pathways in monocytes/macrophages (28,43,47) and synovial (20) and epithelial (46) cells.…”
Section: Cd40 Triggers Inflammatory Pathways In Isletmentioning
confidence: 99%
See 2 more Smart Citations